Diseño de un sistema de contabilidad pecuaria para ganado de leche en la hacienda Rasumar, Ubicada En La Parroquia Toacaso Del Cantón Latacunga, Provincia De Cotopaxi, para el perìodo mayo-julio 2012 - Tapia Román, Marcia Yolanda (2012)
In the present work was designed an accounting system livestock management of cattle for milk production in the Hacienda Rasumar on the basis of a system of in-house accounts for the productive activities has, for which it is determined the technical aspects of currently required to achieve a truthful information that will allow you to achieve planned objectives. We assessed the current handling of finances, which determined the activities carried out raising breeding dairy cattle and milk marketing. The total area was established to be used for the production of milk which is 40 hectares. It was analyzed the processes that are used in the production and marketing of milk which are: the management of cattle, milking, feeding, heath, pasture, etc. Also, we identified major suppliers and customers that will have the farm taking into account the closeness, the demand for dairy industries and benefits, identified the infrastructure necessary for the production of milk. Such as: room milking, pens, feeding trough for water and sleeve of healing. Detailed the diagrams necessary to carry the accounting records of the daily activities of the management of livestock, is a useful tool for the owner in the effective and efficient management of livestock in the implementation of accounting.